How do you simplify #(-12t^-1 u^5 v^-4 )/(2t^-3 u v^5)#?

1 Answer
Apr 7, 2018

Answer:

Simplified: #-(6t^2u^4)/v^9#

Explanation:

Expression: #(-12t^-1u^5v^-4)/(2t^-3uv^5)#

Apply fraction rule #(-a)/b = -a/b#

#=-(12t^-1u^5v^-4)/(2t^-3uv^5)#

Divide the numbers #12/2 = 6#

#=-(6t^-1u^5v^-4)/(t^-3uv^5)#

Apply exponent rule: #x^a/x^b = x^(a-b)#

#=-(6t^2u^5v^-4)/(uv^5)#

Cancel the common factor "u"

#=-(6t^2u^4v^-4)/v^5#

Apply exponent rule: #x^a/x^b=x(a-b)# and #x^-a = 1/x^a#

Answer #=-(6t^2u^4)/v^9#

~ Alex